Cybersecurity Risks in Financial Transactions: Implications for Global Trade and Economic Development - Kundavaram, RamMohan Reddy; Onteddu, Abhishake Reddy; Nizamuddin, Md.; Devarapu, Krishna (Global Disclosure of Economics and Business, 2023)
This research examines financial transaction cybersecurity vulnerabilities and their effects on global commerce and economic growth. The study seeks to understand cyber dangers, financial system vulnerabilities, and economic impact of international trade. The research examines cybersecurity concerns using secondary data from literature, industry reports, and case studies. Phishing, ransomware, and advanced persistent threats (APTs) targeting crucial financial systems, including interbank payment networks and supply chain financing, are becoming more sophisticated. The report also shows that developing countries are susceptible to weak cybersecurity infrastructure and worsening global economic imbalances. The study also emphasizes the relevance of AI, blockchain, and multi-factor authentication in cybersecurity. Policy implications include international collaboration to unify cybersecurity standards and laws and targeted help for developing economies to improve cybersecurity resilience. The research recommends cybersecurity innovation and cross-border cooperation to promote safe and fair global commerce. The results emphasize the need to enhance cybersecurity policies to protect economic stability and promote sustainable growth in a digitalized world.